2019
DOI: 10.1016/j.clon.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Can We Discharge Dynamically Risk-Stratified Low-Risk (Excellent Response to Treatment) Thyroid Cancer Patients After 5 Years of Follow-Up?

Abstract: Aims: The 2014 British Thyroid Association thyroid cancer guidelines recommend lifelong follow-up of thyroid cancer patients. This is probably unnecessary, can cause patient anxiety, is time consuming and places significant demand on National Health Service resources. It has been suggested that low-risk differentiated thyroid cancer (DTC) patients could be discharged to primary care once they are 5 years from diagnosis and treatment. The aim of this study was to investigate the potential safety of this practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…Our findings confirm a remarkable prognosis after an excellent response to treatment upon DRS comparable to previous studies that have shown a risk of 1%–4% tumour recurrence over 5–10 years 8–11 . Importantly, biochemical recurrence became evident in all patients before detection of the structural disease on imaging, although unfortunately, only four patients had ‘curable’ recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings confirm a remarkable prognosis after an excellent response to treatment upon DRS comparable to previous studies that have shown a risk of 1%–4% tumour recurrence over 5–10 years 8–11 . Importantly, biochemical recurrence became evident in all patients before detection of the structural disease on imaging, although unfortunately, only four patients had ‘curable’ recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest that long-term follow-up of Tg in patients with excellent response is needed. A similar study reveals 1.1% of DTC patients with excellent response to initial therapy developed metastatic disease during a median follow-up of 10 years (9). The most common metastatic site was lung in our (71.4%) and that (75.0%) studies.…”
Section: Discussionsupporting
confidence: 78%
“…Patients with excellent response have a low recurrence rate (1-4%) and low mortality rate (<1%) ( 8 ). Therefore, a decrease in the intensity and frequency of follow-up is recommended for patients who have excellent response to initial therapy ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been acknowledged that patients with S/FIR require a more intensive follow-up than those with non-S/FIR (1,17,18). Conversely, a non-S/FIR means a < 1% rate of disease-specific death (1,19). The current study revealed no significant difference in response to RAT among the three risk groups, manifesting that RAT using a high activity of 5.55 GBq can yield similar short-term efficacies among the three-tiered risk groups.…”
Section: Discussionmentioning
confidence: 99%